German fußball—recent developments and origins - Krüger, M.; Herzog, M. (German Journal of Exercise and Sport Research, 2018)
Fußball is the most popular sport in Germany. The reasons for this extraordinary status and success of association football in Germany are complex. In this article, answers are searched for in the context of the historical development of German society. After a review of the recent development of German football and football historiography, the paper focuses on two issues relating to the origins of German football. These are the transformation of football in the then dominant body culture of gymnastics, and secondly its impact on the German process of nation-building. Both processes are not only linked, but also related to the concept of manliness in German sport and society. This is the reason why women`s football in Germany was not accepted until the late 1960s in German society—and British as well.